Complications Associated with Parenteral Nutrition in the Neonate - Calkins, Kara L (Clin Perinatol, 2014)
Parenteral nutrition (PN) is essential to the practice of neonatology. While PN is life-sustaining, it associated with a host of complications including parenteral nutrition-associated liver disease (PNALD) and central line-associated bloodstream infections (CLASBIs), which carry a high morbidity and mortality and pose a burden to the healthcare system. Evidence has emerged that the dose and composition of intravenous lipid products can alter the incidence of PNALD and CLASBIs. However, other patient- and PN-related factors, such as prematurity, birth weight, and gastrointestinal anatomy and function, must not be ignored. In order improve neonatal care, future research is still needed to optimize the content of PN and decrease the incidence PNALD and CLASBIs.